2015
DOI: 10.14785/lpsn-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

The history and evolution of immunoglobulin products and their clinical indications

Abstract: The history of providing antibodies to treat diseases began in the 19th century with the discovery of tetanus and diphtheria toxins and the demonstration that immunity to tetanus and diphtheria infections could be transferred by immune sera. Characterization of the mediators of this immunity resulted in the discovery that antibodies are proteins that can be isolated and used to protect against infectious diseases. Development of a method to isolate antibodies from human plasma that could be safely injected int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…In a landmark paper published in 1890, Emil von Behring with Shibasaburo Kitasato reported that blood taken from rabbits vaccinated with tetanus bacteria and then injected into mice, protected the mice against lethal doses of Clostridium tetani . Shortly thereafter, Von Behring published similar results using Corynebacterium diphtheria infection of guinea pigs . In 1894, Richard Pfeiffer performed in vitro experiments with Vibrio cholera showing that the plasma of previously immunized guinea pigs could lyse the bacteria, terming this the “Pfeiffer's phenomenon” .…”
Section: The Discovery Of Igmmentioning
confidence: 94%
See 3 more Smart Citations
“…In a landmark paper published in 1890, Emil von Behring with Shibasaburo Kitasato reported that blood taken from rabbits vaccinated with tetanus bacteria and then injected into mice, protected the mice against lethal doses of Clostridium tetani . Shortly thereafter, Von Behring published similar results using Corynebacterium diphtheria infection of guinea pigs . In 1894, Richard Pfeiffer performed in vitro experiments with Vibrio cholera showing that the plasma of previously immunized guinea pigs could lyse the bacteria, terming this the “Pfeiffer's phenomenon” .…”
Section: The Discovery Of Igmmentioning
confidence: 94%
“…In 1930, Tiselius developed a technique, later adopted by Landsteiner, to separate and visualize proteins by electrophoresis . Using this technique, Tiselius and Kabat In 1939 identified a major band of serum proteins (γ‐globulins), which we now understand to contain most immunoglobulins …”
Section: The Discovery Of Igmmentioning
confidence: 99%
See 2 more Smart Citations
“…Broader preparations of IVIG or intravenous immunoglobulins were developed, still widely used not only for immunodeficient patients but also for the treatment of such autoimmune disorders as immune thrombocytopenic purpura . Nowadays, IVIG are processed in order to try and limit the adverse reactions they may yield …”
Section: Antibodies or Immunoglobulins?mentioning
confidence: 99%